Real-time analysis of Drosophila post-embryonic haemocyte behaviour. - Christopher J Sampson (Public Library of Science (PLoS), 2012)
Background The larval stage of the model organism Drosophila is frequently used to study host-pathogen interactions. During embryogenesis the cellular arm of the immune response, consisting of macrophage-like cells known as plasmatocytes, is extremely motile and functions to phagocytise pathogens and apoptotic bodies, as well as produce extracellular matrix. The cellular branch of the larval (post-embryonic) innate immune system consists of three cell types--plasmatocytes, crystal cells and lamellocytes--which are involved in the phagocytosis, encapsulation and melanisation of invading pathogens. Post-embryonic haemocyte motility is poorly understood thus further characterisation is required, for the purpose of standardisation. Methodology In order to examine post-embryonic haemocyte cytoskeletal dynamics or migration, the most commonly used system is in vitro cell lines. The current study employs an ex vivo system (an adaptation of in vitro cell incubation using primary cells), in which primary larval or pre-pupal haemocytes are isolated for short term analysis, in order to discover various aspects of their behaviour during events requiring cytoskeleton dynamics. Significance The ex vivo method allows for real-time analysis and manipulation of primary post-embryonic haemocytes. This technique was used to characterise, and potentially standardised, larval and pre-pupal haemocyte cytoskeleton dynamics, assayed on different extracellular matrices. Using this method it was determined that, while larval haemocytes are unable to migrate, haemocytes recovered from pre-pupae are capable of migration.